The Universal Enveloping Ternary Ring of Operators of a JB*-Triple System. Issue 2 (22nd November 2013) - Bohle, Dennis; Werner, Wend
Abstract We associate to every JB*-triple system a so-called universal enveloping ternary ring of operators (TRO). We compute the universal enveloping TROs of the finite dimensional Cartan factors.